Synthesis of aryl acetamides by aminocarbonylation of benzylic chlorides using carbamoylsilane as an amide source. Issue 7 (3rd April 2017) - Zhang, Wenjun; Han, Shenghua; Chen, Jianxin
ABSTRACT: Using N -methyl- N -(1-phenyl)ethylcarbamoyl(trimethyl)silane as an amide source, the direct transformation of benzylic chlorides into the corresponding aryl acetamides through palladium-catalyzed aminocarbonylation is described. The electronic property and the relative position of substituents on the aromatic ring impact the coupling efficiency. GRAPHICAL ABSTRACT: